Effect of the Fluorination of Graphene Nanoflake on the Dispersion and Mechanical Properties of Polypropylene Nanocomposites - Lee, Min Gyu; Lee, Sangwoon; Cho, Jaehyun; Bae, Seokyoung; Jho, Jae Young (MDPI, 2020)
In order to investigate the effect of fluorination of graphene nanoflake on the dispersibility in polypropylene (PP) composites, fluorinated graphene oxide (FGO) was prepared by solvo-thermal reaction and applied as a filler of the PP nanocomposite. Due to the weakened inter-particle attraction among the graphene nanoflake and reduced surface energy difference between PP and the filler, PP/FGO composites showed better exfoliation and dispersion state of the filler compared with that of PP/graphene oxide (GO) or PP/reduced graphene oxide (RGO) composites. The improved exfoliation and dispersion of graphene nanoflake resulted in a significant reinforcement on the composites. The Young's modulus and tensile strength of PP composites filled with 2 wt% of FGO increased by 31% and 15%, respectively, compared with those of PP.